Empiric Therapy with Low-Dose I-131 in Differentiated Cancer Thyroid: What is the Magic Number? - Ajit Shinto; K. Kamaleshwaran; Deepu Shibu; K. Vyshak; Joppy Antony (World Journal of Nuclear Medicine)
Low dose radioactive iodine-131 (RAI) has been widely reported in the treatment of patients with differentiated thyroid cancer (DTC) since 1970′s. However, the clinical outcomes, dosage of I-131 and criteria for successful ablation are different in various studies. The aim of this study was to assess clinical outcome 18-month after RAI therapy in selected DTC patients and identify factors associated with a good response. In this experimental study, among patients with DTC referred to the Nuclear Medicine Department and had an indication for RAI therapy in the period between December 2008 and January 2011, 108 subjects were selected randomly. The patients were randomly divided into three groups and empiric low dose therapy with 30, 50 or 75 mCi of I-131 was administered. Patients were monitored closely clinically and with serum thyroglobulin assays and I-131 whole-body scans at 6 monthly intervals for 18-month after treatment. Among 105 patients who completed follow-up, 86% were successfully ablated with a single low dose of I-131. There was no statistically significant difference in ablation rates in the subgroups receiving 30.50 or 75 mCi of I-131. Cumulative ablation rate was 99% in patients after the second dose of low dose therapy. If appropriate selection criteria are used in DTC, successful remnant ablation can be achieved with low doses of I-131 in the range of 30-75 mCi. No significant differences were found in results achieved with 30.50 or 75 mCi of I-131. As the majority of the DTC patients fall within the inclusion criteria of this study, they can be treated on an ambulatory basis with associated low cost, convenience, and low whole-body radiation-absorbed dose to the patients.